The Effect of Profitability and Competitive Advantage on Corporate Social Responsibility Disclosure - Daylinda, Safira Gusti; Saraswati, Erwin (TEMA, 2025)
Many key factors can influence Corporate Social Responsibility Disclosure (CSRD). This study focuses on two main factors, namely Competitive Advantage (CA) and Profitability. The purpose of this study is to determine how Competitive Advantage (CA) and Profitability, which are independent variables, influence Corporate Social Responsibility Disclosure (CSRD), which is a dependent variable. In addition, Company Size and Leverage serve as control variables in this study. This study uses purposive sampling in selecting samples, namely 42 companies in the manufacturing industry listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022. Secondary data in the form of companies' annual financial reports listed on the Indonesia Stock Exchange (IDX) are used in this study. Hypothesis testing was processed using SPSS software. The results show that simultaneously, Profitability and Competitive Advantage can influence Corporate Social Responsibility Disclosure (CSRD). Partially, Competitive Advantage is proven to be a significant indicator in influencing CSRD, while Profitability does not show a significant effect on Corporate Social Responsibility Disclosure (CSRD).